2020
DOI: 10.1063/1.5134926
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven statistical modeling of the emergent behavior of biohybrid microrobots

Abstract: Multi-agent biohybrid microrobotic systems, owing to their small size and distributed nature, offer powerful solutions to challenges in biomedicine, bioremediation, and biosensing. Synthetic biology enables programmed emergent behaviors in the biotic component of biohybrid machines, expounding vast potential benefits for building biohybrid swarms with sophisticated control schemes. The design of synthetic genetic circuits tailored toward specific performance characteristics is an iterative process that relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Moreover, hybrid control schemes combining centralized and decentralized control strategies can be advantageous. For instance, in the case of targeted drug delivery applications, a decentralized control scheme can be used to prevent off-target cargo release by agents that failed to respond to the centralized control signal to reach the site of interest [61].…”
Section: + Years Of Biohybrid Robots 21 Microorganism-botsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, hybrid control schemes combining centralized and decentralized control strategies can be advantageous. For instance, in the case of targeted drug delivery applications, a decentralized control scheme can be used to prevent off-target cargo release by agents that failed to respond to the centralized control signal to reach the site of interest [61].…”
Section: + Years Of Biohybrid Robots 21 Microorganism-botsmentioning
confidence: 99%
“…When a critical signal concentration is reached, the circuit exhibits a switch-like behavior to an 'activated' state of high signal enzyme production, as well as the transcription of any other downstream genes [64][65][66][67][68][69]. We recently demonstrated that synthetic QS circuits could be used to address the need for engineering sensitive and robust decentralized emergent behaviors in populations of biohybrid microrobots [61,70]. Synthetic biology has also been used to impart other functions, such as creating biohybrid microrobotic sensors [71] and light-based control of cargo release by microrobots [72].…”
Section: + Years Of Biohybrid Robots 21 Microorganism-botsmentioning
confidence: 99%
See 3 more Smart Citations